Pelatihan Penggunaan LaTeX Untuk Penulisan Skripsi Bagi Mahasiswa Program Studi Sarjana Matematika FMIPA Universitas Lampung - Mega Sapitri, Nonik; Sawitri, Riza; Wamiliana; Abdurrahman, Ahmad Faruq (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The purpose of this community service activity is to improve the ability of students of the Bachelor of Mathematics Study Program FMIPA University of Lampung to use LaTeX for thesis writing. LaTeX was chosen because it is able to produce documents with a professional format, especially in managing mathematical equations and document layout. The training was held on October 24, 2024 at the Computer Laboratory ofthe Mathematics Department with 19 fifth semester students participating. The methods used include providing training modules, using LaTeX-based thesis templates, and hands-on practice using the Overleaf platform. The training results showed that 95% of participants recognized theimportance of using LaTeX, with 93% feeling satisfied with the training implementation. However, time efficiency was evaluated with a score of 80%, indicating the need for further training. Participants showed high enthusiasm and were able to practice LaTeX features, including table creation and writing mathematical equations. Through this training, students are equipped with technical skills to produce a thesis that is not only content-quality but also meets academic standards. Thus, this activity supports the strengthening of student competencies while supporting the University of Lampung as a higher education institution that excels in academics and research.